STRATEGI PENANGKARAN PENYU DI UPTD (KPSDKP) KONSERVASI PENGAWASAN SUMBERDAYA KELAUTAN DAN PERIKANAN PROVINSI SUMATERA BARAT - Neneng Marlian; Hayatun Nufus; Nabil Zurba; Yuni Sarah (Universitas Teuku Umar, 2022)
The study was carried out at the Regional Technical Implementation Unit (RTIU) Conservation Monitoring of Marine and Fishery Resources (CMOMFS) of West Sumatera Province. The observation was conducted from January 1st to January 30th 2020. Measurements of sand samples in semi-natural nets and water samples in rearing ponds were conducted ex-situ. The research consisted of several parameters such as humidiy, temperature, depth and diameters of semi-natural nets as well as salinity, pH and water temperature of the rearing pond. Based on the observations, it was found that turtle breeding technique consisted of several stages including, monitoring of the coast, ensuring the depth and diameters of nets, incubation of eggs, hatching eggs, taking the hatchlings from semi-natural nets, nursery hatchlings, feeding hatchlings, rearing hatchlings and turtles and realesing hatchlings. The results showed that the value of humadity, temperature, dept and diameter of semi-natural nets respectively ranged between 4% - 6%, 28 - 35 0C, 40-60 cm and 20 cm. Meanwhile, the value of salinity, temperature and pH of rearing pond water ranged between 13 - 14 ppm, 27 - 28 0C and 7-8. The turtle breeding tecniques were in accordance with the guidelines for turtle conservation and had been generally established. The result of turtle rearing pond water quality measurements were in accordance with the water quality standards according to KepMenLH No. 51 in 2004 concerning Seawater Quality Standards, especially for the categoy of Marine Biota.Keywords: Strategy, Conservation, Turtle, CMOMFS